PENGARUH PEMIJATAN PERINEUM PADA PRIMIGRAVIDA TERHADAP KEJADIAN RUPTUR PERINEUM SAAT PERSALINAN - Desi Afrina Simamora; Lestari Nurul Aulia, Devy; Aidina, Dyka (Universitas Batam, 2025)
The Maternal Mortality Rate (MMR) is still high globally and nationally, with bleeding and infection due to perineal rupture as the main causes. Primigravida are at greater risk of experiencing perineal rupture. Perineal massage has been proven to be effective in increasing tissue elasticity, thereby reducing the incidence of perineal rupture and labor complications. This study aims to determine the effect of perineal massage on primigravida on the incidence of perineal rupture during labor. This study is a quantitative study with a quasi-experimental method with a non-equivalent control group design. The population is all primigravida pregnant women with a gestational age of 34-36 weeks who visit the UPTD Baloi Permai Health Center. The sampling technique used purposive sampling and obtained a sample of 18 respondents. The data obtained were analyzed using SPSS. The results showed that most respondents in the treatment group did not experience perineal rupture (77.8%), while in the control group most experienced second-degree perineal rupture (66.7%). The statistical test obtained a p-value of 0.002 < α 0.05, indicating that perineal massage significantly reduces the incidence of perineal rupture. Healthy pregnant women of reproductive age (20–35 years) are recommended to perform regular perineal massage starting at 34 weeks of gestation using proper technique. This practice increases muscle elasticity, improves blood flow, and prepares the tissues for childbirth, thereby reducing the risk of perineal rupture. Keywords: Perineal massage, rupture, Primigravida